Concept of climate-charged airspace areas - Niklaß, Malte (author); Grewe, V. (author); Gollnick, V (author) (2020)
Approximately two third of aviation’s climate impact is caused by non-CO2 effects, like the production of ozone and the formation of contrail-cirrus clouds, which can be effectively prevented by re-routing flights around highly climate-sensitive areas. Although climate-optimized re-routing results in slightly longer flight times, increased fuel consumption and higher operating costs, it is up to 60% more climate-friendly. However, if mitigation efforts are associated with a direct increase in costs, this immediately raises the question of the willingness of primarily profit-oriented airlines to act in a more climate-friendly manner and the passengers´ willingness to pay for environmental protection. In order to create an incentive for climate-optimized flying, a climate charge is imposed on airlines when operating in these areas. If climate-charged airspaces (CCAs) are (partly) bypassed, both climate impact and operating costs of a flight can be reduced: a more climate-friendly routing becomes economically attractive (explanation video). By implementing the precautionary and polluter-pays principles of environmental economics, the concept introduces key requirements of a sustainable development into the field of aviation. The proposed extension of the accounting system clearly reduces the discrepancy between the marginal costs estimated by the airlines and the consequential costs for society. Accordingly, this resolves the trade-off between economic viability and environmental compatibility and creates a financial incentive for climate mitigation. The feasibility of this concept is demonstrated on a small route network in the North Atlantic flight corridor (NAFC). If flights are completely re-routed around altered CCAs, on average more than 90 % of the mitigation potential of climate-optimized flying is achieved. Aircraft Noise and Climate Effects